ANALISIS PREDIKSI KEBANGKRUTAN PADA EMITEN DENGAN HARGA SAHAM DIBAWAH SERATUS - Fitria, Annisa Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the issuersâ position who issues stock price less than Rp 100.00 whether it shows the company tends to bankrupt or not. This research is qualitative research with descriptive study. The samples have been selected by using purposive sampling. The samples are 15 issuers which are listed in Indonesia Stock Exchange (IDX) with stock price less than Rp100.00. The data collection technique uses documentation method by taking secondary data in the form of financial statement of these companies during five years period (2008-2012) and these financial ratios are calculated then they are used to calculate Altman Z-Score. The result of the research shows that 6 companies or 40% is predicted to undergo bankruptcy, 6 companies or 40% is predicted to be in grey area position or prone bankrupt and 3 companies or 20% is predicted not to bankrupt. Bankruptcy prediction by using Z-Score method has a relation with financial ratio so when a company is predicted to go bankrupt, this problem is supported by company financial ratio is in not good condition. Keywords: Financial Ratio, Bankruptcy Prediction, Z-Score Method, Stock Price